Pengaruh Penggunaan Media Pembelajaran Powerpoint Terhadap Motivasi BelajarSiswa Mata Pelajaran PAI Kelas VIII.I DI SMP Negeri 7 Makassar - Abdurrofi; Elli Oschar; Andi Mulawakkan Firdaus (Advances In Education Journal, 2025)
This study, entitled The Influence of Using PowerPoint as a Learning Mediumon Students’ Learning Motivation in Islamic Religious Education (PAI) forClass VIII.I at SMP Negeri 7 Makassar, was carried out under the supervisionof Elli Oschar and Andi Mulawakkan Firdaus, Faculty of Islamic Studies,Universitas Muhammadiyah Makassar. The purpose of this research is todetermine the extent to which the use of PowerPoint influences students’learning motivation. The study employed a quantitative approach with a sampleof 32 students from Class VIII.I. Data were collected through observation,questionnaires, and documentation. The findings show that the use ofPowerPoint in PAI learning is categorized as high (57.9%), with teacherseffectively utilizing attractive layouts, images, animations, and systematicexplanations. Students’ motivation also increased, as reflected in their interest,enthusiasm, and active participation during lessons. Statistical analysis revealeda positive and significant effect of PowerPoint use on learning motivation,indicated by a significance value of 0.011 (p < 0.05), a regression coefficient of0.669, and a contribution of 33.5% (R² = 0.335), while the remaining 66.5% isinfluenced by other factors. The correlation coefficient (R) of 0.579 furtherconfirms a strong positive relationship between the use of PowerPoint andstudents’ learning motivation. Thus, it can be concluded that PowerPoint has apositive and significant impact on enhancing students’ motivation in learningIslamic Religious Education.